Clinico-epidemiological pattern of determinants of visible disabilities among patients affected with leprosy in Raipur district, Chhattisgarh - Verma, Aashish; Sinha, Ashish Kumar; Jain, Kamlesh Kumar; Verma, Nirmal; Verma, Smita; Dewangan, Pradeep Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: Widespread implementation of MDT has been an extremely successful strategy for leprosy control across the world including India instead of it Chhattisgarh and Dadra & Nagar Haveli are yet to achieve elimination. Identifying the causes of delay in presentation remains a matter of concern, Hence the present study was conducted with intent to assess the clinico-epidemiological patterns of determinants of Leprosy patients with visible disabilities (Grade II disability) in Raipur District of Chhattisgarh. Methods: This community based cross sectional study was conducted in Raipur district during August 2017- October 2019. 87 Newly diagnosed leprosy patients with visible Grade II disabilities registered during 1st April 2016- 31st March 2017 were included in the study. Patient’s information was obtained from their treatment card and was tracked in the community; necessary information was obtained in a predesigned pretested proforma and clinical examination was carried out. Results: Out of 87 study participants, almost are all the subjects had multi-bacillary type of leprosy. The mean duration between appearance of 1st symptoms & diagnosis was 14.59±11.87 months. Conclusions: The current study has observed many gaps in patient care viz. Lack of supervision of treatment, follow up examination and assessment of disability during course of care. Ignorance of early signs and symptoms was found to be the commonest cause of delayed diagnosis.